Direct thermal polymerization approach to N-rich holey carbon nitride nanosheets and their promising photocatalytic H-2 evolution and charge-storage activities - Antil, Bindu; Kumar, Lakshya; Reddy, K. P.; Gopinath, C. S.; Deka, Sasanka (ACS Sustainable Chemistry & Engineering, 2019)
Energy conversion and energy storage are two crucial challenges in green chemistry that have attracted tremendous attention for the last several decades. In this work, we have addressed both issues by synthesizing nitrogen-rich, few-layer-thick holey graphitic carbon nitride (g-C3N4) nanosheets by a simple, novel, direct thermal polymerization method, which is found to be very good in photocatalytic H-2 evolution reaction (energy-conversion) and charge-storage supercapacitor (energy-storage) applications. This as-synthesized conjugated polymer semiconductor (obtained stoichiometry C3N4.8) with unique structural and morphological advantages exhibits superior photocatalytic water splitting activity to H-2 evolution (2 620 mu mol h(-1) g(-1)) without the help of any cocatalysts under visible light in the presence of 20% triethanolamine (TEOA). The calculated apparent quantum yield is 8.5% at 427 nm, and the rate of photocatalytic hydrogen generation remained constant for nine consecutive catalytic cycles (9 h photocatalysis). The present material also shows electrochemical double layer capacitor (EDLC) behavior in alkaline electrolyte, where a symmetric coin cell device consisting of this electrode material without any large area support or conductive filler delivers high specific capacitance (275 F g(-1)), energy density (30 Wh kg(-1)), and power density (6651 W kg(-1)), and the supercapacitor cell can retain >98% capacitance efficiency up to 10 000 measured cycles at various current densities.
Keywords: g-C3N4; Hydrogen evolution; nanosheets; Photocatalyst; supercapacitor; water splitting

One-dimensional multichannel g-C3N4.7 nanostructure realizing an efficient photocatalytic hydrogen evolution reaction and its theoretical investigations - Antil, Bindu; Kumar, Lakshya; Ranjan, Ravi; Shenoy, Sulakshana; Tarafder, Kartick; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Applied Energy Materials, 2021)
The emerging metal-free carbon nitride (C3N4) offers prominent possibilities for realizing the highly effective hydrogen evolution reaction (HER). However, its poor surface conductivity and insufficient catalytic sites hinder the HER performance. Herein, a one-dimensional vermicular rope-like graphitic carbon nitride nanostructure is demonstrated that consists of multichannel tubular pores and high nitrogen content, which is fabricated through a cost-effective approach having the final stoichiometry g-C3N4.7 for HER application. The present g-C3N4.7 is unique owing to the presence of abundant channels for the diffusion process, modulated surface chemistry with rich- electroactive sites from N-electron lone pairs, greatly reduced recombination rate of photoexcited exciton pairs, and a high donor concentration (4.26 x 10(17) cm(3)). The catalyst offers a visible-light-driven photocatalytic H-2 evolution rate as high as 4910 mu mol h(-1)g(-1) with an apparent quantum yield of 14.07% at band gap absorption (2.59 eV, 479 nm) under 7.68 mW cm(-2) illumination. The number of hydrogen gas molecules produced is 1.307 x 10(15) s(-1) cm(-2), which remained constant for a minimum of 18 h of repeated cycling in the HER without any degradation of the catalyst. In density functional theory calculations, a significant change in the band offset is observed due to N doping into the system in favor of electron catalysis. The theoretical band gap of a monolayer of g-C3N4.7 was enormously reduced because of the presence of additional densities of states from the doped N atom inside the band gap. These impurity or donor bands are formed inside the band gap region, which ultimately enhance the hydrogen ion reduction reaction enormously.
Keywords: carbon nitride; Density functional theory; hydrogen evolution reaction; nitrogen-rich; Photocatalyst